Zooming in on the Formation of Protoplanetary Disks. Issue Volume 8:Issue S299(2013) (6th January 2014) - Nordlund, Åke; Haugbølle, Troels; Küffmeier, Michael; Padoan, Paolo; Vasileiades, Aris
Abstract: We use the adaptive mesh refinement code RAMSES to model the formation of protoplanetary disks in realistic star formation environments. The resolution scales over up to 29 powers of two (~ 9 orders of magnitude) covering a range from outer scales of 40 pc to inner scales of 0.015 AU. The accretion rate from a 1.5 solar mass envelope peaks near 10 −4 M⊙ about 6 kyr after sink particle formation and then decays approximately exponentially, reaching 10 −6 M⊙ in 100 kyr. The models suggest universal scalings of physical properties with radius during the main accretion phase, with kinetic and / or magnetic energy in approximate balance with gravitational energy. Efficient accretion is made possible by the braking action of the magnetic field, which nevertheless allows a near-Keplerian disk to grow to a 100 AU size. The magnetic field strength ranges from more than 10 G at 0.1 AU to less than 1 mG at 100 AU, and drives a time dependent bipolar outflow, with a collimated jet and a broader disk wind.